The impact of atmospheric pollutants on the physical health of college students based on physical examination data of college students from a university in Xi’an, Shaanxi Province, China - He, Jiaxin; Liu, Ke; He, Zhiyu (Frontiers in Public Health, 2025)
BackgroundAir pollution, particularly particulate matter (PM2.5/PM10), poses a significant environmental health threat in urban China. While previous research has primarily focused on older adult populations, the impact of air pollution on college students—an important yet underexplored demographic—remains largely unclear. This study investigates the effects of air pollutants on physical fitness and lung function among students at a university in Xi’an, a city known for its persistent air quality challenges.MethodsWe used longitudinal physical examination data (2019–2022) from 21,580 college students to perform empirical correlation regression and kernel density estimation. Trends in physical fitness and vital capacity scores were analyzed alongside air quality indicators (AQI, PM2.5, PM10, CO). A mixed cross-sectional econometric model controlled for individual characteristics such as height (mean = 170.66 cm, SD = 8.37), weight (mean = 64.94 kg, SD = 13.40), gender (mean = 0.313, SD = 0.464), and environmental factors such as temperature, wind speed, and green coverage (mean = 41.22, SD = 1.45). Physical fitness scores exhibited high variability (SD = 9.62, range = 10.2–109).ResultsAir pollution was significantly associated with a reduction in physical fitness scores. A 1-unit increase in the AQI was linked to a 0.1094-unit decline in fitness scores (p < 0.01). The negative effect was further amplified by PM2.5 (β = −0.2643) and CO (β = −11.5438). Senior students, especially females, showed increased vulnerability to the adverse effects of pollution. Trends in lung capacity mirrored those in physical fitness, with outliers suggesting individual susceptibility. Notably, reduced green coverage was found to mediate 22% of the health impact of pollution (p < 0.05).ConclusionThis study highlights the disproportionate health impact of air pollution on college students, emphasizing the need for policies that focus on reducing emissions, expanding campus greenery, and promoting health education. Future research should incorporate individual fixed effects and broaden the study to include a wider range of regions and universities.